Enhanced Grain Iron Levels in Rice Expressing an IRON-REGULATED METAL TRANSPORTER, NICOTIANAMINE SYNTHASE, and FERRITIN Gene Cassette - Boonyaves, Kulaporn; Wu, Ting-Ying; Gruissem, Wilhelm; Bhullar, Navreet K. (Frontiers in Plant Science, 2017)
Micronutrient malnutrition is widespread, especially in poor populations across the globe, and iron deficiency anemia is one of the most prevalent forms of micronutrient deficiencies. Iron deficiency anemia has severe consequences for human health, working ability and quality of life. Several interventions including iron supplementation and food fortification have been attempted and met with varied degrees of success. Rice, which is a staple food for over half of the world’s population, is an important target crop for iron biofortification. The genetic variability of iron content in the rice germplasm is very narrow, however, and conventional breeding has not been successful in developing high iron rice varieties. Therefore, genetic engineering approaches have targeted at increasing iron uptake, translocation and storage in the rice endosperm. We previously reported that AtIRT1, when expressed together with AtNAS1 and PvFERRITIN (PvFER) in high-iron (NFP) rice, has a synergistic effect of further increasing the iron concentration of polished rice grains. We have now engineered rice expressing AtIRT1, AtNAS1 and PvFER as a single locus gene cassette and compared the resulting lines with transgenic lines expressing AtIRT1 and PvFER gene cassettes. We also evaluated the efficacies of the MsENOD12B and native AtIRT1 promoters for the expression of AtIRT1 in rice in both types of gene cassettes, and found the native AtIRT1 promoter to be a better choice for driving the AtIRT1 expression in our biofortification strategy. All the single insertion transgenic lines have significant increases of iron concentration, both in polished and unpolished grains, but the concerted expression of AtIRT1, AtNAS1 and PvFER resulted to be a more effective strategy in achieving the highest iron increases of upto 10.46 µg g-1 DW. Furthermore, the transformed high iron lines grew better under iron deficiency growth conditions and also have significantly increased grain zinc concentration. Together, these rice lines have nutritionally relevant increases in polished grain iron and zinc concentration necessary to support human health.